2014
DOI: 10.1371/journal.pone.0097009
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Improves Plaque Stability in ApoE-Knockout Mice by Regulating Chemokines and Chemokine Receptors

Abstract: It is well documented that statins protect atherosclerotic patients from inflammatory changes and plaque instability in coronary arteries. However, the underlying mechanisms are not fully understood. Using a previously established mouse model for vulnerable atherosclerotic plaque, we investigated the effect of atorvastatin (10 mg/kg/day) on plaque morphology. Atorvastatin did not lower plasma total cholesterol levels or affect plaque progression at this dosage; however, vulnerable plaque numbers were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 24 publications
5
45
3
Order By: Relevance
“…The authors of a recent study using apolipoprotein E-knockout mice found that the addition of Atorvastatin to a high fat diet decreased LDL cholesterol levels in the blood, as expected, but also decreased the GGT expression in the plaque at the same time [150]. To us, this suggests that there is a reduced need for GGT to promote sulfate synthesis because there is insufficient cholesterol in the blood to be conjugated with it to form cholesterol sulfate.…”
Section: Ggt In the Synovium: An Explanationsupporting
confidence: 56%
“…The authors of a recent study using apolipoprotein E-knockout mice found that the addition of Atorvastatin to a high fat diet decreased LDL cholesterol levels in the blood, as expected, but also decreased the GGT expression in the plaque at the same time [150]. To us, this suggests that there is a reduced need for GGT to promote sulfate synthesis because there is insufficient cholesterol in the blood to be conjugated with it to form cholesterol sulfate.…”
Section: Ggt In the Synovium: An Explanationsupporting
confidence: 56%
“…Immunohistochemistry staining was performed as described (Jin et al, 2012;Nie et al, 2014). Briefly, frozen sections were fixed with 4% paraformaldehyde at 4°C for 20 min, permeabilized with 0.2% Triton X-100 for 10 min at room temperature and blocked with 5% BSA IL-6, MMP13, TNF-α, and CCL2) were normalized to β-actin.…”
Section: Immunofluorescencementioning
confidence: 99%
“…Classically, it has been believed that the site of this anti‐inflammatory action is on the blood‐borne side of the arterial wall, i.e. statins suppress the inflammation that results from hypercholesterolaemia and the imbibing of oxidized lipoproteins across a dysfunctional coronary artery endothelium . However, in recent years, investigators have proposed that the primary site of the anti‐inflammatory benefit of statins may be in the adventitia, specifically in the perivascular adipose tissue that surrounds the coronary arteries .…”
Section: Anti‐inflammatory Effects Of Statins In Heart Failurementioning
confidence: 99%
“…statins suppress the inflammation that results from hypercholesterolaemia and the imbibing of oxidized lipoproteins across a dysfunctional coronary artery endothelium. 28,29 However, in recent years, investigators have proposed that the primary site of the anti-inflammatory benefit of statins may be in the adventitia, specifically in the perivascular adipose tissue that surrounds the coronary arteries. 30,31 The distribution of epicardial fat is focally asymmetric, and intriguingly, focal obstructive lesions develop in the coronary arterial segments that are immediately adjacent to areas of epicardial fat with the greatest thickness.…”
Section: Anti-inflammatory Effects Of Statins In Heart Failurementioning
confidence: 99%